2004
DOI: 10.1096/fj.03-0502fje
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II in ischemia/reperfusion‐induced leukocyte‐endothelium interactions in the colon

Abstract: The aims of the present study were to determine the effects and mechanisms of angiotensin II (Ang II) on leukocyte-endothelium interactions and the role of Ang II in a novel model of ischemia/reperfusion (I/R) in the mouse colon. Ang II dose-dependently increased leukocyte rolling and adhesion in colonic venules. Importantly, Ang II-induced leukocyte rolling was completely inhibited by immunoneutralization of P-selectin, and leukocyte adhesion was abolished in lymphocyte function antigen-1 (LFA-1)-deficient mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
(41 reference statements)
4
39
0
1
Order By: Relevance
“…[12,14] Activation of these receptors causes an increase in inflammatory response. [12,[16][17][18][19] Losartan, which is an angiotensin type 1 (AT1) receptor blocker, has antiinflammatory properties via acting on local systems. Zhu and Sato et al showed this drug's ability to reduce the area of infarction in the myocardium.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[12,14] Activation of these receptors causes an increase in inflammatory response. [12,[16][17][18][19] Losartan, which is an angiotensin type 1 (AT1) receptor blocker, has antiinflammatory properties via acting on local systems. Zhu and Sato et al showed this drug's ability to reduce the area of infarction in the myocardium.…”
Section: Resultsmentioning
confidence: 99%
“…[20,21] Moreover, losartan prevents ischemia-reperfusion injury in many organs including the heart, [16,22] liver, [12] lungs, [23] endothelium, [24] brain, [25] and large intestine. [19] We hypothesize that ischemic damage in the skin may also be decreased if proinflammatory properties of angiotensin were inhibited. In this study, the effects of losartan on ischemic skin flaps and its possible role in improving flap survival were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations